A Nanoarchitecture Based on Silver and Copper Oxide with an Exceptional Response in the Chlorine‐Promoted Epoxidation of Ethylene. Issue 37 (12th July 2016) - Ramirez, Adrian; Hueso, Jose L.; Suarez, Hugo; Mallada, Reyes; Ibarra, Alfonso; Irusta, Silvia; Santamaria, Jesus
Abstract: The selective oxidation of ethylene to ethylene epoxide is highly challenging as a result of competing reaction pathways leading to the deep oxidation of both ethylene and ethylene oxide. Herein we present a novel catalyst based on silver and copper oxide with an excellent response in the selective oxidation pathway towards ethylene epoxide. The catalyst is composed of different silver nanostructures dispersed on a tubular copper oxide matrix. This type of hybrid nanoarchitecture seems to facilitate the accommodation of chlorine promoters, leading to high yields at low reaction temperatures. The stability after the addition of chlorine promoters implies a substantial improvement over the industrial practice: a single pretreatment step at ambient pressure suffices in contrast with the common practice of continuously feeding organochlorinated precursors during the reaction. Abstract : When silver meets copper oxide : A catalyst composed of silver nanostructures dispersed within a nanotubular copper oxide support was found to be an excellent catalyst for the selective epoxidation of ethylene at temperatures below 250 °C. The catalyst can accommodate chlorine promoters in a single pretreatment step with the CuO acting essentially as a Cl sponge, thus avoiding, for the most part, irreversible catalyst poisoning.